Plant small RNA : biogenesis, regulation and application - Guleria, Praveen; Kumar, Vineet (Academic Press, 2020)
Plant Small RNA: Biogenesis, Regulation and Application describes the biosynthesis of small RNA in plant systems. With an emphasis on the various molecular mechanisms affected by small RNA and their applications in supporting plant growth and survival, this books presents the basics and most recent advancements in small RNA mediated plant genomics, metabolomics, proteomics and physiology. In addition, it emphasizes the various molecular mechanisms affected by small RNA and their applications in supporting plant growth and survival. Final sections cover the most recent advancements in small RNA mediated plant genomics, metabolomics, proteomics and physiology. --